Low energy electrons and swift ion track structure in PADC - Fromm, Michel (2015)
The current work aims at providing an accurate description of the ion track-structure in poly-allyl dyglycol carbonate (PADC) by using an up-to-date Monte-Carlo code-called TILDA-V (a French acronym for Transport d'Ions Lourds Dans l'Aqua & Vivo). In this simulation the ion track-structure in PADC is mainly described in terms of ejected electrons with a particular attention done to the Low Energy Electrons (LEEs). After a brief reminder of the most important channels through which LEEs are prone to break a chemical bond, we will report on the simulated energetic distributions of LEEs along an ion track in PADC for particular incident energies located on both sides of the Bragg-peak position. Finally, based on the rare data dealing with LEEs interaction with polymers or organic molecules, we will emphasise the role played by the LEEs in the formation of a latent track in PADC, and more particularly the one played by the sub-ionization electrons.